For young and future generations?: Insights from the web profiles of european climate pact ambassadors - Tosun, Jale; Geese, Lucas; Lorenzoni, Irene (European journal of risk regulation, 2023)
The European Climate Pact provides opportunities for individuals, communities and organisations to declare their commitment to climate action. This study analyses the publicly available web profiles of the European Climate Pact Ambassadors (PAs) as of January 2023. First, it explores the extent to which people who volunteer as PAs demonstrate commitment to young and future generations. Second, it investigates whether PAs who self-identify as young people are more likely than other PAs to justify their mandate by referring to the interests of young and future generations. Third, it examines whether PAs who self-identify as young people are more likely to indicate other young people as the target audience of their activities. The manual coding and quantitative analysis of the PAs’ web profiles revealed that members of older generations as well as parents and grandparents are most likely to rationalise their engagement in the programme by referring to young and future generations. The data also showed that young people do target other young people when they act as PAs, but they are not the only group to do so. When compared to individuals with other professional identities, educators are also more likely to flag young people as their target audience.